2016
DOI: 10.1002/hbm.23451
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of trust in reciprocity: A coordinate‐based meta‐analysis

Abstract: Trust in reciprocity (TR) is defined as the risky decision to invest valued resources in another party with the hope of mutual benefit. Several fMRI studies have investigated the neural correlates of TR in one-shot and multi-round versions of the investment game (IG). However, an overall characterization of the underlying neural networks remains elusive. Here, we employed a coordinate-based meta-analysis (activation likelihood estimation method, 30 papers) to investigate consistent brain activations in each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 129 publications
13
112
0
Order By: Relevance
“…Our findings bolster the assertion that trust propensity is a complex social construct emerging from the interactions among large‐scale networks (Bellucci, Chernyak, Goodyear, Eickhoff, & Krueger, ; Fehr, ). In line with this assumption, a recent study employing resting‐state brain‐electrical connectivity revealed that trust propensity could be predicted by connections of electrodes located over the frontal and parietal regions (Hahn et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Our findings bolster the assertion that trust propensity is a complex social construct emerging from the interactions among large‐scale networks (Bellucci, Chernyak, Goodyear, Eickhoff, & Krueger, ; Fehr, ). In line with this assumption, a recent study employing resting‐state brain‐electrical connectivity revealed that trust propensity could be predicted by connections of electrodes located over the frontal and parietal regions (Hahn et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…In the social domain, the CON has been shown to support control processes for strategic behavior (Hahn, Notebaert, Anderl, Reicherts, et al, 2015b). Moreover, task-based fMRI studies reveal that CON regionssuch as the anterior insula and anterior cingulate cortexare recruited during reciprocity decisions in the TG (Bellucci et al, 2017(Bellucci et al, , 2018Chang, Smith, Dufwenberg, & Sanfey, 2011; Features predicting reciprocity behavior. Cingulo-opercular network (CON) (A), default-mode network (DMN) (B), and frontoparietal network (FPN) (C) regions of interest (ROIs) and edges selected across the cross-validation procedure to predict reciprocal behavior (on the left).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two different game settings were used in those studies: the multi-round TG in the EEG study (in which participants repeatedly played with different players) and the one-round TG in the fMRI study (in which participants made only one, single-trust decision for each player). The different natures of the social interactions reproduced by these two TG versions have been shown to engage different cognitive processes (Bellucci, Chernyak, Goodyear, Eickhoff, & Krueger, 2017;Bellucci, Feng, Camilleri, Eickhoff, & Krueger, 2018). Therefore, the contribution of single RSFC networks in predicting trusting and reciprocal behaviors in the same TG version to date remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Together, the above results establish these regions as prime candidates for investigations of the modulatory effects of incidental aversive emotion on mentalizing during trust decisions. In addition, we explored the effects of incidental aversive emotion on neural activity in the anterior insula, which has consistently been implicated in both aversive emotion 49,50 and trust decisions 51 , and the amygdala, which has consistently 52 and relatively specifically (neurosynth reverse inference analysis for "aversive") been implicated in the processing 15 and regulation of aversive emotions 53 , and at the same time plays a central role in trustworthiness inferences 54,55 .…”
mentioning
confidence: 99%